THE EFFECT OF READING INTERESTS IN THE LIBRARY ON LEARNING OUTCOMES AT GRADE IV SD NEGERI 7 PARDUGUL IN ACADEMIC YEAR 2020/2021 - Lenni Tampubolon; Rumiris Lumban Gaol; Ester Simarmata; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed to determine the effect of reading interest in the library on the learning outcomes at grade IV SD Negeri 7 Pardugul in the academic year 2020/2021. The population was 50 students and all of them were chosen as the samples of this study. This research utilized a quantitative method with a survey type. The method used in this research was a quantitative method. Then, the hypotheses were tested by using t test. The results of this study showed that there was a significant effect of reading interests in the library on the learning outcomes of the fourth grade students at SD Negeri 7 Pardugul in the academic year 2020/2021. This finding was supported by the value of tcount > ttable, which was 3.204 > 1.675. Hence, H0 was accepted, meaning that there was a significant effect of reading interests on students’ learning outcomes. Based on the results of this study, it can be concluded that reading interests has an effect on students’ learning outcomes.